2020
DOI: 10.3390/molecules25030682
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Allicin-Free Garlic on Gut Microbiome

Abstract: The allicin diallyldisulfid-S-oxide, a major garlic organosulfur compound (OSC) in crushed garlic (Allium sativum L.), possesses antibacterial effects, and influences gut bacteria. In this study, we made allicin-free garlic (AFG) extract and investigated its effects on gut microbiome. C57BL/6N male mice were randomly divided into 6 groups and fed normal diet (ND) and high-fat diet (HFD) supplemented with or without AFG in concentrations of 1% and 5% for 11 weeks. The genomic DNAs of feces were used to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…In both assays, diets supplemented with garlic positively impacted GM, as supplementation succeeded in restoring the number of beneficial bacteria to the gut health of mice, such as Lachnospiraceae and Akkermansia, whose counts had been reduced by HFD. The administration of AFG extract was able to reduce the increase in the F/B ratio caused by HFD, relieving the negative impact of this diet on the health of animals and their inflammatory response [62]. The mice that consumed whole garlic in the latter study, showed a greater regulation of the diversity of GM, which led to revert the reduction of Bacteroidetes and beneficial species of the genus Prevotella caused by HFD [69].…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…In both assays, diets supplemented with garlic positively impacted GM, as supplementation succeeded in restoring the number of beneficial bacteria to the gut health of mice, such as Lachnospiraceae and Akkermansia, whose counts had been reduced by HFD. The administration of AFG extract was able to reduce the increase in the F/B ratio caused by HFD, relieving the negative impact of this diet on the health of animals and their inflammatory response [62]. The mice that consumed whole garlic in the latter study, showed a greater regulation of the diversity of GM, which led to revert the reduction of Bacteroidetes and beneficial species of the genus Prevotella caused by HFD [69].…”
Section: Discussionmentioning
confidence: 76%
“…In two studies carry out in mice with dyslipidemia induced by HFD, the administration of Allium products derived from garlic showed an attenuation of the harmful effects caused by this diet on GM [62,69]. In one of these assays, whole garlic was administered [69], while, in the other one, the Allium product tested was an allicin-free garlic extract (AFG) [62]. In both assays, diets supplemented with garlic positively impacted GM, as supplementation succeeded in restoring the number of beneficial bacteria to the gut health of mice, such as Lachnospiraceae and Akkermansia, whose counts had been reduced by HFD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations